2018
DOI: 10.1007/s11365-018-0544-1
|View full text |Cite
|
Sign up to set email alerts
|

Managing collaborative ideation: the role of formal and informal appropriability mechanisms

Abstract: Collaborative ideation is a key practice for innovation. Implementing suitable appropriability mechanisms during this collaborative ideation is a necessary yet difficult task. This difficulty owes to a high level of uncertainty and low level of codification because partners work on loosely defined concepts that may change during the collaboration. Firms can employ several appropriability mechanisms to protect their knowledge. Examples include patents, copyright, legal agreements, document management, lead time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 58 publications
(73 reference statements)
0
5
0
3
Order By: Relevance
“…In other studies, property rights were identified as a significant barrier towards involving external sources in ideation [68]. Gama [69] argues that different formal and informal appropriation methods are combined for collaborative ideation. Therefore, the activity 'define results transfer mode' needed to be added in phase (2).…”
Section: Demonstrate Artifactmentioning
confidence: 98%
“…In other studies, property rights were identified as a significant barrier towards involving external sources in ideation [68]. Gama [69] argues that different formal and informal appropriation methods are combined for collaborative ideation. Therefore, the activity 'define results transfer mode' needed to be added in phase (2).…”
Section: Demonstrate Artifactmentioning
confidence: 98%
“…Specifically, IP operation consists of working to decide whether to protect innovation outcome, identify which type of IP tools they should use, whether there is possible IP commercialization, and any IP management process required. Unlike strategic planning, such an operating resource represents realized appropriation capabilities at the operational level due to its evidence of clear ownership [18,43,47].…”
Section: The Moderating Role Of Ip Operationmentioning
confidence: 99%
“…For value protection, isolating mechanisms are most commonly used [50]. These include both formal mechanisms-such as patents, copyrights and intellectual property rights, and formal contracts-and informal mechanisms such as confidentiality, secrecy, or hidden knowledge [51][52][53]. The value protected in this way does not increase the economic rent, but it rather aims to limit losses.…”
Section: Value Creation and Appropriation And Durability As The Attribute Of The Relational Strategymentioning
confidence: 99%